Effect of PECVD SiNx deposition process parameters on electrical properties of SiNx/AlGaN/GaN structures - Kira L. Enisherlova (Pensoft Publishers, 2021)
The effect of parameters of plasma enhanced chemical vapor deposition (PECVD) processes for SiNx film fabrication on the electrical parameters of dielectric/АlGaN/GaN structures has been studied. The effect of growing film composition, additional heterostructure surface treatment with nitrogen plasma before dielectric deposition and HF biasing during treatment on the parameters of the С–V and I–V curves of SiNx/АlGaN/GaN structures has been analyzed. We show that films with nitrogen to silicon concentration ratios of 60 and 40% and a high oxygen content exhibit a decrease in the positive fixed charge in the structures although the I–V curves of the structures exhibit current oscillations. Information has been reported on the effect of PECVD process mode on current oscillation parameters, e.g. period and amplitude, and length of I–V curve section in which oscillations occur. Possible explanation of these oscillations has been suggested. Additional nitrogen plasma treatment of heterostructure surface before monosilane supply to the chamber changes the magnitude and sign of fixed charge and reduces the free carrier concentration in the 2D gas channel of SiNx/АlGaN/GaN heterostructures. Experimental evidence has been provided for the effect of PECVD process parameters and surface preparation on the electrical parameters of the heterostructures grown.